Telegram, 1928 June 12, to Stultz, Trepassey, Newfoundland - Putnam, George Palmer, 1887-1950 (Purdue University Libraries, Archives and Special Collections, 1928)
George Palmer Putnam telegram to Wilmer Stultz, weather and suggested flight path, June 12, 1928